Contesting Culture: The Grammar of 'Kaala'. Issue 2 (December 2020) - Menon, Shailaja
Cinema as an art form vividly captures the aspirations and everyday life-worlds of the people in India. In more contemporary times, suffused with the global language of desire, popular Indian cinema has sought to project the nation as a global power, while invisibilizing the faultiness of caste, gender, race and ethnicity. The films are increasingly shot in exotic locales with the lead characters leading enchanted lives. Innovative technology is utilized to narrate stories in which the farmer/worker/maid/other laboring people are conspicuous by their absence. Very few films possess the courage to buck this trend to recount tales of struggle entwined with the language of rights and justice. My article focuses on one such film—Pa Ranjith's Kaala (Black). The film interrogates the muscular religiosity, caste and patriarchy on which the nation state is tethered. The cinematic journey also infuses the locale of Dharavi in Mumbai, home to thousands of migrant workers, with an agency of its own.